2020
DOI: 10.3389/fnins.2020.00751
|View full text |Cite
|
Sign up to set email alerts
|

A Radiomics Approach to Predicting Parkinson’s Disease by Incorporating Whole-Brain Functional Activity and Gray Matter Structure

Abstract: Parkinson's disease (PD) is a progressive, chronic, and neurodegenerative disorder that is primarily diagnosed by clinical examinations and magnetic resonance imaging (MRI). In this study, we proposed a machine learning based radiomics method to predict PD. Fifty healthy controls (HC) along with 70 PD patients underwent restingstate magnetic resonance imaging (rs-fMRI). For all subjects, we extracted five types of 6664 features, including mean amplitude of low-frequency fluctuation (mALFF), mean regional homog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 52 publications
0
42
0
Order By: Relevance
“…Another study used the Harvard–Oxford atlas to extract the mean ReHo, ALFF, VMHC, gray matter volume, and FC features. The authors found that both random forest (accuracy = 0.8261, AUC = 0.9015) and support vector machine (accuracy = 0.8483, AUC = 0.9697) achieved the perfect accuracy and AUC for distinguishing between PD and HC subjects (Cao et al, 2020 ). Our results are better than those of these studies, which may indicate that our histogram analysis method can extract more information in the ROIs (Lambin et al, 2012 ; Gillies et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study used the Harvard–Oxford atlas to extract the mean ReHo, ALFF, VMHC, gray matter volume, and FC features. The authors found that both random forest (accuracy = 0.8261, AUC = 0.9015) and support vector machine (accuracy = 0.8483, AUC = 0.9697) achieved the perfect accuracy and AUC for distinguishing between PD and HC subjects (Cao et al, 2020 ). Our results are better than those of these studies, which may indicate that our histogram analysis method can extract more information in the ROIs (Lambin et al, 2012 ; Gillies et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…We used the same imaging data from the same recruited subjects as in our previously published issue (Cao et al., 2020). The only difference is that we further stratify the PD patients into two groups of DPD and NDPD to examine the aberrant functional connectivity and activity in DPD and to build machine learning models for predicting DPD and NDPD.…”
Section: Methodsmentioning
confidence: 99%
“…A radiomic study based on PET/CT images extracted high‐order features and trained a SVM model to classify PD and HC subjects, and the results demonstrated that the radiomic method combined with SVM could distinguish PD from HC (Wu et al., 2019). Cao et al leveraging rs‐fMRI radiomic features showed that machine learning methods including Lasso and SVM could significantly improve diagnostic accuracy of PD (Cao et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, even the main neural and pathophysiological mechanisms of PD are the degeneration of the nigrostriatal dopaminergic system; it cannot fully explain the heterogeneity of symptoms ( Tuovinen et al, 2018 ; Sheng et al, 2021 ). The exact mechanism of PD is still not well understood ( Tuovinen et al, 2018 ; Cao et al, 2020 ; Lin et al, 2020 ; Sheng et al, 2021 ). Therefore, quantifiable biomarkers are urgently needed for a more comprehensive understanding of the physiological mechanism of PD and improving the diagnosis accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…It can detect the amplitude of spontaneous, low-frequency oscillations of blood oxygen level-dependent signals to reflect the regularity and physiological state of neuron autonomous activity in different brain regions ( Qian et al, 2020 ). This approach provides a reliable and sensitive measurement to characterize the spontaneous neural activity and has been widely used in PD ( Cao et al, 2020 ; Tian et al, 2020 ; Pang et al, 2021 ; Shi et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%